Ethanol sensing characteristics of ZnO nanostructures impregnated by gold colloid - Wongrat E. (2014)
ZnO nanostructures were synthesized by thermal oxidation reaction from zinc powder and then impregnated by gold colloid. The gold colloid was prepared by chemical reduction technique and had red color. The heating temperature and sintering time of thermal oxidation were 700 °C and 24 hours, respectively under oxygen atmosphere. The morphology of ZnO nanostructures and ZnO impregnated gold colloid were studied by field emission scanning electron microscope (FE-SEM). The diameter and length of pure ZnO and ZnO impregnated gold colloid were about the same value and were in the range of 100-500 nm and 2.0-7.0 μm, respectively. The ethanol sensing properties of ZnO impregnated by gold colloid were tested in ethanol atmosphere at ethanol concentrations of 1000 ppm and at an operating temperature of 260-360 °C. It was found that the sensitivity and response time were improved for gold impregnated sensor with an optimum operating temperature of 300° C due to the enhanced reaction between the ethanol and the adsorbed oxygen at an optimum temperature. © 2008 Trans Tech Publications, Switzerland.